Phytochemical Screening and Antibacterial Activity of Leaf Extracts of Gymnema sylvestre against Pathogenic Bacteria - Ramadass, N.; Subramanian, N.; Ponnulakshmi, R.; Selvaraj, J. (International Journal of Scientific Research in Biological Sciences, 2019)
The aim of our present study to investigate the phytochemical screening and antibacterial activity of Etholnolic and Chloroform leaf extracts of Gymnema sylvestre against some important pathogenic bacteria. The Ethonoloic and Choloroform leaf extracts of G.sylvestre showed significant antibacterial against some clinically important gram negative and gram positive bacteria such as Staphylococcus aureus (ATCC6538), Enterococcuc faecalis (ATCC 29212) and Escheria coli (ATCC8739), Salmonella enterica (ATCC 10798) respectively. The in-vitro antibacterial activity was performed by agar well diffusion method (25, 50, 75 and 100 µg/ml ). The maximum inhibition zone of ethonolic leaf extract was found in 100 µg /ml against gram negative bacteria such as Salmonella enterica (26mm), Escheria coli (24mm) and gram positive bacteria such as Enterocococcus faecalis (26mm) and Staphylococcus aureus (24mm). The maximum inhibition zone of chloroform leaf extracts found in 100 µg/ml (25,50,75, and 100 µg/ ml) against gram negative bacteria such as Salmonella enterica (24mm), Escheria coli (24mm) and gram positive bacteria Enterocococcus faecalis (23mm) and Staphylococcus aureus (23mm). The phytochemical tests were carried out and showed that the antibacterial activity of plant Gymnema sylvestre leaves were due to presence of phytochemical compounds such as Alkaloids, Flvanoids, Glycosides, Reducing sugar, Tannins, Saponins, Polysaccharides and Phenols. The ethonolic and choloroform leaf extracts of Gymnema sylvestre showed maximum inhibition against Staphylococcus aureus, Enterocococcus faecalis, Salmonella enterica and Escheriacoli. The Ciprofloxacin was used as a positive control.